2004
DOI: 10.1103/physreve.69.066110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adaptive cruise control systems on traffic flow

Abstract: The flow of traffic composed of vehicles that are equipped with adaptive cruise control (ACC) is studied using simulations. The ACC vehicles are modeled by a linear dynamical equation that has string stability. In platoons of all ACC vehicles, perturbations due to changes in the lead vehicle's velocity do not cause jams. Simulations of merging flows near an onramp show that if the total incoming rate does not exceed the capacity of the single outgoing lane, free flow is maintained. With larger incoming flows, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(126 citation statements)
references
References 24 publications
2
123
0
1
Order By: Relevance
“…This technology is substantially more complex than conventional cruise control; ACC adjusts the brake and/or throttle, within limited ranges, to maintain a constant headway from any vehicle that intrudes upon the path of the driver's vehicle. While ACC provides a potential safety benefit in helping drivers maintain a constant speed and headway (Davis, 2004), as with other types of automation, there is the potential for misuse and disuse (Parasuraman and Riley, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This technology is substantially more complex than conventional cruise control; ACC adjusts the brake and/or throttle, within limited ranges, to maintain a constant headway from any vehicle that intrudes upon the path of the driver's vehicle. While ACC provides a potential safety benefit in helping drivers maintain a constant speed and headway (Davis, 2004), as with other types of automation, there is the potential for misuse and disuse (Parasuraman and Riley, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous traffic simulation studies of ACC can also be found in the literature (Minderhoud and Bovy, 1999;Hoogendoorn and Minderhoud, 2002;Davis, 2004Davis, , 2007van Arem et al, 2006;Kesting et al, 2007aKesting et al, , 2007b. Traffic simulation has traditionally been applied for quality-of-service analysis of proposed changes in traffic management or road network design.…”
Section: Adaptive Cruise Control and Car-followingmentioning
confidence: 99%
“…Several driver behavioural studies of driving with ACC have been performed (Dragutinovic et al, 2005;Saad et al, 2004). ACC has also been the subject of many traffic simulation experiments (Minderhoud and Bovy, 1999;Hoogendoorn and Minderhoud, 2002;Davis, 2004Davis, , 2007van Arem et al, 2006;Kesting et al, 2007aKesting et al, , 2007b. Most traffic simulation studies of ACC impacts have focused on macroscopic capacity and quality-of-service impacts of the distance keeping functionality of the ACC.…”
Section: Introductionmentioning
confidence: 99%
“…An Adaptive Cruise Control (ACC) system is a radar-based system that extends the conventional cruise control system and that is designed to sense the vehicle immediately in front on the same lane, and to automatically adjust the speed of the equipped vehicle to that of the preceding vehicle so as to maintain a safe inter-vehicle distance [28,29]. If there is no predecessor, then ACC retains the preset speed that was selected by driver.…”
Section: Adaptive Cruise Controlmentioning
confidence: 99%